(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
A transformational philosophy based on truth (Satya), non-violence (Ahimsa), self-reliance (Swadeshi) and inclusiveness, Sarvodaya philosophy closely parallels to the philosophy of Mahatma Gandhi whose philosophy is Sarvodaya or Welfare for all. Sarvodaya, which traces its origins from its interpretation of John Ruskin’s Unto This Last, is a society where dignity is respected, equality is observed and harmony prevails. The philosophy is a belief in decentralized governance through Gram Swaraj, (the place of the people), community development and empowering marginalized groups. Critical to understanding modern challenges such as poverty, income inequality, and environmental degradation is that Gandhi emphasized local production, ethical consumption, and minimalism. Sarvodaya stretches beyond limits of historic reality and becomes a formative force in the social justice and environmental stewardship and pacifist movements of the world. Principles of NMTA’s are consistent with modern paradigms as embodied by the United Nations’ Sustainable Development Goals (SDGs) and promote a well balanced view attending both to individual and collective well being. Sarvodaya is a timeless philosophy that frames a way of organizing inclusive and sustainable societies all over the globe.